Remote, direct-manipulation interaction for multi-user, web-based public display interfaces - Maria João Barreira (2014)
The presence of digital public-displays in urban landscapes has increased, however only few ofthem allow a direct-manipulation to passersby. Nowadays, the main feature is advertise a serviceor a product and often, people ignore them. It is importante to be centered in final user and allowan easier developement of applications that provide an efficient interaction for one or more users.